A review of activating lattice oxygen of metal oxides for catalytic reactions: Reaction mechanisms, modulation strategies of activity and their practical applications - Du, Heng; Luo, Haopeng; Jiang, Mingwei; Yan, Xing; Jiang, Fang; Chen, Huan (Applied catalysis. A, General, 2023)
Lattice oxygen is increasingly attracting the attention of researchers as an active site in metal oxide catalysts. This paper reviews the strategies used in recent years to regulate the activity of lattice oxygen in catalysts and its application in catalytic reactions. It begins by exploring the mechanisms of lattice oxygen in various reactions, then provides a systematic overview of techniques employed to enhance the activity of catalysts, such as inactive A-site cation substitution, B-site cation substitution, the design of shell-core structures, and post-treatment of existing catalysts. Finally, the practical applications of these methods are discussed, including electrocatalytic reactions, advanced oxidation processes, and removal of volatile organic compounds. This review provides technical guidance for lattice oxygen-based metal oxide catalysts in oxygen vacancy modulation and provides a reference for future researchers interested in exploring the transformation of lattice oxygen in the reaction. [Display omitted] •Mechanism of lattice oxygen involvement in driving redox reactions.•Different strategies can be used to adjust the concentration of oxygen vacancies in the catalyst to change the lattice oxygen activity.•Recent advances in lattice oxygen redox reactions for environmental applications.